Method for preparing double-metal cyanide catalyst through dynamic release and double-metal cyanide catalyst
Through the dynamic release preparation method, the complexing agent is used to control the slow release of zinc ions, which solves the problems of uneven particle size distribution and poor catalytic activity of the bimetallic cyanide catalyst during the preparation process, and achieves a catalyst with high activity, short induction period and uniform particle size, improving the safety and stability of production.
Patent Information
- Application Number
- CN202510115132.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
During the preparation process, existing bimetallic cyanide catalysts have problems such as uneven particle size distribution, poor catalytic activity, long induction period, and difficult to control production safety and stability.
The dynamic release preparation method is adopted to form chelates through complexing agent and cyanide-free metal salt, and the reaction of the slow release of zinc ions and the metal cyanide salt is controlled to form uniform catalyst particles.
The catalyst is achieved with high activity, short induction period, uniform particle size distribution and low viscosity, which improves the safety and stability of production, and is suitable for the synthesis of propylene oxide and ethylene oxide polyether.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of double metal cyanide catalysts, and more specifically, to a method for preparing a double metal cyanide catalyst by dynamic release and a double metal cyanide catalyst. Background Art
[0002] The preparation of double metal cyanide catalysts by precipitation reaction of an aqueous solution of a cyanide-free metal salt with an aqueous solution of a metal cyanide salt is a common method at present. Generally speaking, the precipitation reaction includes at least two stages. The first is the nucleation stage, in which a large number of primary seeds are formed by homogeneous nucleation or heterogeneous nucleation and precipitated from the solution. The nucleation reaction rate and ion morphology mainly depend on the supersaturation of the primary nuclei in the solution, temperature, stirring factors, etc. The second is the stage in which the primary nuclei continue to grow, or aggregate with each other to form larger particles. When the nucleation rate is much higher than the nuclear growth rate, it is conducive to the formation of a large number of small-sized, monodispersed particles; when the nuclear growth rate is much higher than the nucleation rate, it is conducive to the formation of large-sized particles; but when the difference between the two speeds is small, the two proceed simultaneously to form a wider particle size distribution.
[0003] Although the coprecipitation reaction appears to be an instantaneous process, from the perspective of the stirred tank reaction itself, there is still a distribution gradient in the local concentration. The nucleation reaction and the growth reaction proceed simultaneously, which can easily cause the aggregation and inactivation of the catalyst particles and the uneven particle size distribution, which will inevitably lead to great differences in catalytic activity. This makes it necessary to have an obvious dormant period when using it to prepare polyethers. During this period, the highly active part has triggered some reactions but the low-activity part is still in a dormant state, which is often undesirable for actual production. On the one hand, it prolongs the production time (sometimes up to ten hours). On the other hand, various side reactions are likely to occur during the induction period, affecting the purity of the target product. Finally, the end of the induction period is often accompanied by a rapid drop in pressure and a sharp increase in temperature, affecting production safety and stability.
[0004] At the same time, due to the heterogeneity of the catalytic activity, the molecular weight distribution of the obtained polyether is relatively wide, and even obvious tailing phenomenon occurs at the high molecular weight, which makes the polyether have a higher viscosity, which is also undesirable in use.
[0005] In US Pat. No. 5,482,908, a DMC catalyst prepared by using a mixture of tert-butyl alcohol and ethylene glycol dimethyl ether as an organic complex has a certain degree of improvement in catalytic activity and a certain degree of shortening induction time. However, there is a phenomenon of excessive temperature rise at the moment of induction, and the temperature is difficult to control in actual production, which may easily cause production accidents.
[0006] Chinese patent CN201880043922.7 enhances the catalytic activity for small molecule alcohols and multifunctional alcohols by introducing Group 3-15 metals or lanthanide metals, but the induction time is still long, and the monodispersity of the product is poor, and high molecular weight polyethers exist. Summary of the invention
[0007] The present application provides a method for preparing a double metal cyanide catalyst by dynamic release and a double metal cyanide catalyst. The double metal cyanide catalyst prepared by the present application has high catalytic activity, almost no induction period, can use various low molecular weight initiators, can be used for the synthesis of propylene oxide and can be used for the synthesis of ethylene oxide polyether. It also has the advantages of simple process, safe and controllable, low cost, etc.
[0008] In a first aspect, the present application provides a method for preparing a double metal cyanide catalyst by dynamic release, using the following technical solution: A method for preparing a double metal cyanide catalyst by dynamic release, comprising the following steps: Weigh a cyanide-free metal salt and a complexing agent, dissolve them in deionized water, and stir to react to form a solution Sol-A; in the solution Sol-A, the molar ratio of the complexing agent to the cyanide-free metal salt is (0.2-0.5):1, and the mass concentration of the cyanide-free metal salt is 2-10%; the complexing agent includes at least one of an aminocarboxylate complexing agent, a hydroxycarboxylate complexing agent, an organic phosphonate complexing agent, and an inorganic phosphate complexing agent; Weighing a metal cyanide salt and an organic ligand and dissolving them in deionized water to form a solution Sol-B; in the solution Sol-B, the mass concentration of the metal cyanide salt is 1-5%, and the mass concentration of the organic ligand is 2-5%; Sol-A is dropped into Sol-B under stirring to react and obtain a reaction dispersion; the mass ratio of Sol-A to Sol-B is 1:(0.95-1.05); The reaction dispersion is filtered to separate a paste, and the obtained paste is washed until the potassium ion content in the filtrate is less than 5 ppm; The obtained solid was dried and pulverized to obtain catalyst powder.
[0009] Further, the aminocarboxylate complexing agent includes at least one of ethylenediaminetetraacetate, diethylenetriaminepentacarboxylate, and sodium nitrilotriacetate. Still further, the hydroxycarboxylate complexing agent includes at least one of citric acid, sodium citrate, tartaric acid, sodium tartrate, gluconic acid, sodium gluconate, malic acid, and salicylic acid. The organic phosphonate complexing agent includes at least one of ethylenediaminetetramethylenephosphonic acid sodium, diethylenetriaminepentamethylenephosphonic acid sodium, and aminetrimethylenephosphonic acid sodium. The inorganic phosphate complexing agent includes at least one of sodium tripolyphosphate, sodium pyrophosphate, and sodium hexametaphosphate.
[0010] Furthermore, the organic ligand includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octadecanol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, and mannitol.
[0011] Further, the reaction dispersion is filtered and separated to obtain a paste, and the obtained paste is preliminarily washed with a mixture of an organic ligand and water, the preliminarily washing is repeated 1-3 times, and then deep washing is performed with an organic ligand until the potassium ion content in the filtrate is less than 5 ppm.
[0012] Furthermore, the metal salt is a substance having the general formula (I): L(H)e (I) Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ One of: H is selected from Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 One of the carboxylate, nitrate and nitrite ions; When H is sulfate, carbonate or oxalate, e is 1; When H is Cl, Br, cyanate, thiocyanate or nitrate, C 1~4 For carboxylate and nitrite, e is 2.
[0013] Further, the metal cyanide salt is a substance having the general formula (II): X f M b (CN) c (II) Wherein, X is selected from one or more of alkali metals and alkaline earth metals; M is selected from one of Fe, Co, Mn and Ni ions; and f, b and c are selected to meet the requirement of positive and negative charge balance.
[0014] In a second aspect, the present application provides a double metal cyanide catalyst, which adopts the following technical solution: A double metal cyanide catalyst prepared by the above-mentioned method for preparing a double metal cyanide catalyst by dynamic release, wherein the double metal cyanide catalyst is a compound of general formula (III): L a [M b (CN) c ] d·xL(H) e ·yT (III) Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ ; M is selected from one of Fe, Co, Mn, and Ni ions; H is Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 One of carboxylate, nitrate and nitrite ions; T is an organic ligand selected from one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octadecanol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol and mannitol; the selection of a, b, c, d and e meets the requirement of positive and negative charge balance; the value range of x is 0.5-2; the value range of y is 1-3.
[0015] In summary, this application has the following beneficial effects: 1. The present application adopts a complexing agent to form a chelate with zinc ions added to the reaction system, controls the addition amount of each substance, and controls the balance between dropwise addition-chelation-release-reaction, so that the zinc ions are slowly released and generated in the entire solution, and the entire system achieves molecular-level mixing. The released zinc ions react with metal cyanide salts in situ to obtain catalyst particles with a smaller average particle size and excellent monodispersity. When used to prepare polyethers, the catalyst particles have higher activity, almost no obvious induction period, and the obtained product has a narrow molecular weight distribution, no high molecular weight tailing peak, and lower viscosity.
[0016] 2. The present application significantly improves the reaction uniformity, overcomes the problems of uneven distribution of the dropwise reaction products, large composition differences and low activity in the traditional process, and the prepared double metal cyanide catalyst has a more uniform chemical composition, crystalline structure and particle size distribution, and has the advantages of simple process, safe and controllable, and low cost.
[0017] 3. The present invention has higher activity when used to prepare polyethers, and no obvious induction period exists for either a high molecular weight initiator or a low molecular weight initiator. The molecular weight distribution of the obtained product is narrow, there is no high molecular weight tailing peak, and the viscosity is lower, which overcomes the problem that the existing catalyst is not suitable for low molecular weight initiators. DETAILED DESCRIPTION
[0018] The present application is further described in detail below in conjunction with embodiments. Example
[0019] In the examples of the present application, the composition of the catalyst is determined by combining elemental analysis with ICP (inductively coupled plasma atomic emission spectroscopy) analysis; the Zn and Co element contents in the catalyst are determined by an IRIS Advantage full-spectrum direct-reading plasma atomic emission spectrometer, and the C, H, and N elements in the catalyst are determined by an Element Vario EL elemental analyzer.
[0020] Specifically, the present invention provides a method for preparing a double metal cyanide catalyst by dynamic release, comprising the following steps: Weigh the cyanide-free metal salt and the complexing agent, dissolve them in deionized water, and stir to react to form a solution Sol-A; in the solution Sol-A, the molar ratio of the complexing agent to the cyanide-free metal salt is (0.2-0.5):1, and the mass concentration of the cyanide-free metal salt is 2-10%. The reaction temperature is room temperature.
[0021] Weigh a metal cyanide salt and an organic ligand and dissolve them in deionized water to form a solution Sol-B; in the solution Sol-B, the mass concentration of the metal cyanide salt is 1-5%, and the mass concentration of the organic ligand is 2-5%; the reaction temperature is room temperature.
[0022] Sol-A is added dropwise to Sol-B under vigorous stirring to react and obtain a reaction dispersion liquid. The stirring speed is 800-2000 rpm, preferably 900 rpm in this embodiment. The mass ratio of Sol-A to Sol-B is 1:(0.95-1.05); The reaction dispersion is filtered and separated to obtain a paste, and the obtained paste is washed until the potassium ion content in the filtrate is less than 5 ppm; specifically, the obtained paste is preliminarily washed with a mixture of an organic ligand and water, the preliminary washing is repeated 1-3 times, and then the organic ligand is used for deep washing until the potassium ion content in the filtrate is less than 5 ppm.
[0023] The obtained solid is dried and crushed to obtain catalyst powder, usually at a temperature of 20-100°C and under reduced pressure.
[0024] Furthermore, the complexing agent includes at least one of an aminocarboxylate complexing agent, a hydroxycarboxylate complexing agent, an organic phosphonate complexing agent, and an inorganic phosphate complexing agent.
[0025] Among them, the aminocarboxylate complexing agent includes at least one of ethylenediaminetetraacetate, diethylenetriamine pentacarboxylate, and sodium nitrilotriacetate. The hydroxycarboxylate complexing agent includes at least one of citric acid, sodium citrate, tartaric acid, sodium tartrate, gluconic acid, sodium gluconate, malic acid, and salicylic acid. The organic phosphonate complexing agent includes at least one of ethylenediaminetetramethylenephosphonic acid sodium, diethylenetriaminepentamethylphosphonic acid sodium, and aminetrimethylphosphonic acid sodium. The inorganic phosphate complexing agent includes at least one of sodium tripolyphosphate, sodium pyrophosphate, and sodium hexametaphosphate.
[0026] Furthermore, the organic ligand includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octadecanol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, and mannitol.
[0027] Furthermore, the metal salt is a substance having the general formula (I): L(H)e (I) Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ One of: H is selected from Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 One of the carboxylate, nitrate and nitrite ions; When H is sulfate, carbonate or oxalate, e is 1; When H is Cl, Br, cyanate, thiocyanate or nitrate, C 1~4 When it is carboxylate or nitrite, e is 2. The metal salt used in the examples of the present application is zinc chloride.
[0028] Further, the metal cyanide salt is a substance having the general formula (II): X f M b (CN) c (II) Wherein, X is selected from one or more of alkali metals and alkaline earth metals; M is selected from one of Fe, Co, Mn, and Ni ions; and f, b, and c are selected to meet the requirements of positive and negative charge balance. The metal cyanide salt in the embodiment of the present application is K3[Co(CN)6] or K3[Fe(CN)6].
[0029] The double metal cyanide catalyst prepared by the above preparation method is a compound of general formula (III): La [M b (CN) c ] d ·xL(H) e ·yT (III) Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ ; M is selected from one of Fe, Co, Mn, and Ni ions; H is Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 One of carboxylate, nitrate and nitrite ions; T is an organic ligand selected from one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octadecanol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol and mannitol; the selection of a, b, c, d and e meets the requirement of positive and negative charge balance; the value range of x is 0.5-2; the value range of y is 1-3.
[0030] The following is an explanation through specific embodiments. Example 1
[0031] Weigh 4.5 g ZnCl2, 2.77 g chelating agent EDTA-2Na and 92.73 g deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0032] Weigh 1.5 g of K3[Co(CN)6], 2.5 g of organic ligand tert-butyl alcohol and 96.00 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0033] At room temperature and under vigorous stirring, an equal amount of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol dissolved in 150 ml of water). After repeated washing for 3 times, the paste was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain catalyst powder DMC-1.
[0034] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 1.45 Zn(Cl)2 • 1.88 TBA. Example 2
[0035] Weigh 5.3 g of ZnCl2, 3.31 g of complexing agent sodium citrate and 91.39 g of deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0036] Weigh 2.5 g of K3[Fe(CN)6], 3.3 g of organic ligand n-butanol and 94.20 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0037] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-2.
[0038] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 1.49 Zn(Cl)2 • 2.13 TBA. Example 3
[0039] Weigh 9.10 g of ZnCl2, 4.81 g of tartaric acid (a complexing agent) and 86.09 g of deionized water into a flask, and stir to dissolve to obtain a solution Sol-A.
[0040] Weigh 4.5 g of K3[Fe(CN)6], 3.5 g of organic ligand isopropanol and 92.0 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0041] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-3.
[0042] Its composition calculated from the results of elemental analysis and ICP measurement is Zn3[Co(CN)6]2 • 1.33 Zn(Cl)2 • 2.23 TBA. Example 4
[0043] Weigh 2.20 g of ZnCl2, 2.11 g of complexing agent sodium aminotri(methylenephosphonate) and 95.69 g of deionized water into a flask, and stir to dissolve to obtain solution Sol-A.
[0044] Weigh 3.2 g of K3[Co(CN)6], 4.1 g of organic ligand tert-butyl alcohol and 92.7 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0045] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-4.
[0046] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 1.15 Zn(Cl)2 • 1.09 TBA. Example 5
[0047] Weigh 2.50 g of ZnCl2, 3.14 g of complexing agent sodium hexametaphosphate and 94.36 g of deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0048] Weigh 3.5 g of K3[Co(CN)6], 4.5 g of organic ligand tert-butyl alcohol and 92.0 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0049] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-5.
[0050] Its composition calculated from the results of elemental analysis and ICP measurement is Zn3[Co(CN)6]2 • 0.83 Zn(Cl)2 • 2.85 TBA. Example 6
[0051] Weigh 3.30 g of ZnCl2, 2.23 g of complexing agent sodium tripolyphosphate and 94.47 g of deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0052] Weigh 2.5 g of K3[Co(CN)6], 2.7 g of organic ligand tert-butyl alcohol and 94.8 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0053] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-6.
[0054] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 0.64 Zn(Cl)2 • 2.49 TBA. Example 7
[0055] Weigh 3.5 g ZnCl2, 2.16 g chelating agent EDTA-2Na and 94.34 g deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0056] Weigh 4.6 g of K3[Fe(CN)6], 2.2 g of organic ligand isopropanol and 93.20 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0057] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-7.
[0058] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 1.67 Zn(Cl)2 • 1.96 TBA. Example 8
[0059] Weigh 5.5 g ZnCl2, 3.39 g chelating agent EDTA-2Na and 91.11 g deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0060] Weigh 3.5 g of K3[Co(CN)6], 3.5 g of organic ligand tert-butyl alcohol and 93.00 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0061] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-8.
[0062] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 1.33 Zn(Cl)2 • 2.51 TBA. Example 9
[0063] Weigh 4.5 g ZnCl2, 2.77 g chelating agent EDTA-2Na and 92.73 g deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0064] Weigh 1.8 g of K3[Co(CN)6], 3.4 g of organic ligand isopropanol and 94.80 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0065] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-9.
[0066] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 0.95 Zn(Cl)2 • 2.86 TBA. Example 10
[0067] Weigh 2.5 g of ZnCl2, 1.54 g of complexing agent EDTA-2Na and 95.96 g of deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0068] Weigh 3.5 g of K3[Co(CN)6], 2.5 g of organic ligand tert-butyl alcohol and 94.00 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0069] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-10.
[0070] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 1.68 Zn(Cl)2 • 2.56 TBA. Embodiment 11
[0071] Weigh 3.8 g of ZnCl2, 2.34 g of complexing agent EDTA-2Na and 93.86 g of deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0072] Weigh 2.7 g of K3[Co(CN)6], 2.5 g of organic ligand tert-butyl alcohol and 94.80 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0073] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-11.
[0074] Its composition calculated from the results of elemental analysis and ICP measurement is Zn3[Co(CN)6]2 • 1.23 Zn(Cl)2 • 1.85 TBA. Example 12
[0075] Weigh 5.1 g of ZnCl2, 3.14 g of complexing agent EDTA-2Na and 91.76 g of deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0076] Weigh 3.5 g of K3[Co(CN)6], 2.5 g of organic ligand tert-butyl alcohol and 94.00 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0077] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-12.
[0078] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 1.445 Zn(Cl)2 • 2.35 TBA. Comparative Example 1
[0079] Weigh 4.5 g of ZnCl2 and 95.5 g of deionized water into a flask and stir to dissolve to obtain solution Sol-A.
[0080] Weigh 1.5 g of K3[Co(CN)6], 2.5 g of organic ligand tert-butyl alcohol and 96.00 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0081] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-13.
[0082] Its composition calculated by elemental analysis and ICP measurement results is Zn3[Co(CN)6]2 • 0.89 Zn(Cl)2 • 2.36 TBA. Comparative Example 2
[0083] Weigh 4.5 g of ZnCl2, 1.66 g of complexing agent EDTA-2Na and 93.84 g of deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0084] Weigh 1.5 g of K3[Co(CN)6], 2.5 g of organic ligand tert-butyl alcohol and 96.00 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0085] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was preliminarily washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-14.
[0086] Its composition calculated from the results of elemental analysis and ICP measurement is Zn3[Co(CN)6]2 • 1.15 Zn(Cl)2 • 2.18 TBA. Comparative Example 3
[0087] Weigh 4.5 g ZnCl2, 8.88 g chelating agent EDTA-2Na and 86.62 g deionized water into a flask, stir and dissolve to obtain solution Sol-A.
[0088] Weigh 1.5 g of K3[Co(CN)6], 2.5 g of organic ligand tert-butyl alcohol and 96.00 g of deionized water into a flask, stir and dissolve to obtain solution Sol-B.
[0089] At room temperature and under vigorous stirring, an equal mass of Sol-A was slowly dripped into Sol-B using a peristaltic pump. The solution gradually turned from light blue to milky white. The paste was separated by filtration and filtered under reduced pressure. The paste was initially washed with a mixture of tert-butyl alcohol (TBA) and water (150 ml of tert-butyl alcohol was dissolved in 150 ml of water). After repeating the washing three times, it was deeply washed with tert-butyl alcohol until the potassium ion content in the filtrate was less than 5 ppm. Finally, the solid was vacuum dried at 40-60°C and crushed to obtain the catalyst powder DMC-15.
[0090] Its composition calculated from the results of elemental analysis and ICP measurement is Zn3[Co(CN)6]2 • 1.21 Zn(Cl)2 • 2.38 TBA. Performance Testing
[0091] The catalysts in the examples and comparative examples were tested for performance, wherein the specific surface area was tested using the BET method, the crystallinity was tested using XRD, and the catalytic activity was tested using a ring-opening reaction test on propylene oxide. The test results are shown in Table 1: Table 1 Physical properties of the synthesized catalysts sample <![CDATA[Specific surface area m 2 / g]]> <![CDATA[Catalytic activity 10 4 g / g]]> Crystallinity% Example 1 23.6 7.1 5.3 Example 2 19.4 6.8 9.4 Example 3 18.5 6.6 8.2 Example 4 15.3 7.1 6.4 Example 5 15.6 9.3 6.2 Example 6 19.5 5.4 5.9 Example 7 16.4 6.8 6.1 Example 8 17.2 5.4 9.1 Example 9 17.1 9 7.3 Example 10 17.9 7.6 9.4 Embodiment 11 23.4 5 9.3 Example 12 16.8 6.2 5.1 Comparative Example 1 11.3 0.6 12.8 Comparative Example 2 12.1 1.7 11.5 Comparative Example 3 10.9 0.9 8.3 The performance of the comparative example and comparative example 1 is analyzed and found that after not using a complexing agent, the various aspects of the performance of the catalyst of the present application have declines to varying degrees. This is because in the preparation process of the catalyst of the present application, the complexing agent can form a chelate with the zinc ion added to the reaction system, and the balance between the dropwise addition-chelation-release-reaction is controlled, so that the zinc ion is slowly released and generated in the whole solution, and the whole system reaches the mixing of the molecular level, and the released zinc ion reacts with the metal cyanide salt in situ to obtain a smaller average particle size, and the catalyst particles with excellent monodispersity simultaneously overcome the uneven distribution of the dropwise addition reaction product in the traditional process, the large composition difference and the low activity, and the prepared double metal cyanide catalyst has a more uniform chemical composition, crystalline structure and particle size distribution. In addition, in the use of a complexing agent, it can be reflected by the performance of comparative examples 2 and 3 that the consumption of the complexing agent is too much or too little, which is not conducive to improving the performance of the catalyst. Application Examples
[0092] The following application examples 1-12 disclose experimental data of the catalytic effect of the catalyst obtained in Examples 1-12 in various initiator catalytic reactions. Comparative application examples 1-12 disclose experimental data of the catalytic effect of the catalyst obtained in Comparative Examples 1-3 in various initiator catalytic reactions. The catalyst particle size in the application examples and comparative application examples is 5-100 microns. Application Example 1
[0093] 100 g of polyoxypropylene triol (Mn=300) and 0.03 g of catalyst DMC-1 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 1567 g of ethylene oxide was continuously added to obtain the product. Application Example 2
[0094] 100 g of hydroxypropyl methacrylate and 0.05 g of catalyst DMC-2 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 800 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 2500 g of ethylene oxide was continuously added to obtain the product. Application Example 3
[0095] 100 g of hydroxyethyl acrylate and 0.05 g of catalyst DMC-3 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 800 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 2600 g of ethylene oxide was continuously added to obtain the product. Application Example 4
[0096] 100 g of 3-butyn-1-ol and 0.09 g of catalyst DMC-4 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 1000 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 4323 g of ethylene oxide was continuously added to obtain the product. Application Example 5
[0097] 100 g of polyoxypropylene triol (Mn=450) and 0.02 g of catalyst DMC-5 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 600 g of ethylene oxide was continuously added to obtain the product. Application Example 6
[0098] 100 g of methyl allyl alcohol and 0.01 g of catalyst DMC-6 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 5586 g of ethylene oxide was continuously added to obtain the product. Application Example 7
[0099] 100 g of 2-chloroethanol and 0.012 g of catalyst DMC-7 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 6100 g of ethylene oxide was continuously added to obtain the product. Application Example 8
[0100] 100 g of isopentenol and 0.07 g of catalyst DMC-8 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 3499 g of ethylene oxide was continuously added to obtain the product. Application Example 9
[0101] 100 g of diethylene glycol monovinyl ether and 0.05 g of catalyst DMC-99 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 3532 g of ethylene oxide was continuously added to obtain the product. Application Example 10
[0102] 100 g of glycerol and 0.08 g of catalyst DMC-10 were added to a pressure reactor, which was vacuumed and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 3800 g of ethylene oxide was continuously added to obtain the product. Application Example 11
[0103] 100 g of hydroxypropyl acrylate and 0.03 g of catalyst DMC-11 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 1166 g of ethylene oxide was continuously added to obtain the product. Application Example 12
[0104] 100 g of hydroxyethyl methacrylate and 0.07 g of catalyst DMC-12 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 3281 g of ethylene oxide was continuously added to obtain the product. Comparative application example 1
[0105] 100 g of polyoxypropylene triol (Mn=300) and 0.03 g of catalyst DMC-13 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 1567 g of ethylene oxide was continuously added to obtain the product. Comparative Application Example 2
[0106] 100 g of polyoxypropylene triol (Mn=300) and 0.03 g of catalyst DMC-14 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 1567 g of ethylene oxide was continuously added to obtain the product. Comparative Application Example 3
[0107] 100 g of polyoxypropylene triol (Mn=300) and 0.03 g of catalyst DMC-15 were added to a pressure reactor, which was evacuated and heated to 120°C. After 20 g of ethylene oxide was added, the pressure in the reactor reached 0.1 MPa. The pressure was maintained at 120°C and stirred at 500 RPM. The pressure change was observed. When the pressure dropped to 0.05 MPa, the induction period was considered to be over. At this time, 1567 g of ethylene oxide was continuously added to obtain the product. Comparative Application Examples 4-6
[0108] The difference between comparative application examples 4-6 and application example 2 is that the catalysts are replaced in sequence with catalyst DMC-13, catalyst DMC-14, and catalyst DMC-15 in an amount equal to that of DMC-2. Comparative Application Examples 7-9
[0109] The difference between comparative application examples 7-9 and application example 3 is that the catalysts are replaced in sequence with catalyst DMC-13, catalyst DMC-14, and catalyst DMC-15 in an amount equal to that of DMC-3. Comparative Application Examples 10-12
[0110] The difference between comparative application examples 10-12 and application example 4 is that the catalysts are replaced in sequence with catalyst DMC-13, catalyst DMC-14, and catalyst DMC-15 in an amount equal to that of DMC-4. Application example performance testing
[0111] The performance tests are carried out for the corresponding use cases and comparative application cases, as follows: Table 2 Application examples and comparative application example data
[0112] It can be seen from the test results of application examples 1-12 that, whether for macromolecular initiators or small molecule initiators, the catalyst of the present application has almost no obvious induction period when polyether is used, and the molecular weight distribution of the obtained product is narrow, there is no high molecular weight tailing peak, and the viscosity is lower. In addition, the analysis of comparative application examples 1-3 found that compared with the catalyst prepared using the embodiments of the present application, the comparative application examples 1-3 used the catalyst of comparative examples 1-3, and the final effect was much lower than that of the application examples. In addition, the analysis of the test results of comparative application examples 7-12 found that when a small molecular weight initiator was used, the catalyst of the comparative example could not induce a reaction within 24 hours, that is, the induction time required more than 24 hours, which is basically equivalent to no reaction. It can be seen that the catalyst prepared by the preparation method of the present application overcomes the problems of uneven distribution of the dropwise reaction products, large composition differences and low activity in the traditional process. The prepared double metal cyanide catalyst has a more uniform chemical composition, crystalline structure and particle size distribution, and is more active when used to prepare polyethers. Whether it is a large molecular weight initiator or a small molecular weight initiator, there is almost no obvious induction period. The prepared product has a narrow molecular weight distribution, no high molecular weight tailing peak, and a lower viscosity.
[0113] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a double metal cyanide catalyst by dynamic release, characterized in that: The following steps are involved: Weigh a cyanide-free metal salt and a complexing agent, dissolve them in deionized water, and stir to react to form a solution Sol-A; in the solution Sol-A, the molar ratio of the complexing agent to the cyanide-free metal salt is (0.2-0.5):1, and the mass concentration of the cyanide-free metal salt is 2-10%; the complexing agent includes at least one of an aminocarboxylate complexing agent, a hydroxycarboxylate complexing agent, an organic phosphonate complexing agent, and an inorganic phosphate complexing agent; Weighing a metal cyanide salt and an organic ligand and dissolving them in deionized water to form a solution Sol-B; in the solution Sol-B, the mass concentration of the metal cyanide salt is 1-5%, and the mass concentration of the organic ligand is 2-5%; Sol-A is dropped into Sol-B under stirring to react and obtain a reaction dispersion; the mass ratio of Sol-A to Sol-B is 1:(0.95-1.05); The reaction dispersion is filtered to separate a paste, and the obtained paste is washed until the potassium ion content in the filtrate is less than 5 ppm; The obtained solid was dried and pulverized to obtain catalyst powder.
2. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: The aminocarboxylate complexing agent includes at least one of ethylenediaminetetraacetate, diethylenetriaminepentacarboxylate and sodium nitrilotriacetate.
3. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: The hydroxycarboxylate complexing agent includes at least one of citric acid, sodium citrate, tartaric acid, sodium tartrate, gluconic acid, sodium gluconate, malic acid and salicylic acid.
4. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: The organic phosphonate complexing agent includes at least one of ethylenediaminetetra-methylenephosphonic acid sodium, diethylenetriaminepenta-methylenephosphonic acid sodium, and aminetri-methylenephosphonic acid sodium.
5. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: The inorganic phosphate complexing agent includes at least one of sodium tripolyphosphate, sodium pyrophosphate and sodium hexametaphosphate.
6. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: The organic ligand includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octadecanol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, and mannitol.
7. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: The reaction dispersion is filtered and separated to obtain a paste, and the obtained paste is preliminarily washed with a mixture of an organic ligand and water. The preliminarily washing is repeated 1 to 3 times, and then deep washing is performed with an organic ligand until the potassium ion content in the filtrate is less than 5 ppm.
8. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: Metal salts are substances having the general formula (I): L(H)e (I) Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ One of: H is selected from Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 One of the carboxylate, nitrate and nitrite ions; When H is sulfate, carbonate or oxalate, e is 1; When H is Cl, Br, cyanate, thiocyanate or nitrate, C 1~4 For carboxylate and nitrite, e is 2.
9. The method for preparing a double metal cyanide catalyst by dynamic release according to claim 1, characterized in that: Metal cyanide salts are substances having the general formula (II): X f M b (CN) c (II) Wherein, X is selected from one or more of alkali metals and alkaline earth metals; M is selected from one of Fe, Co, Mn and Ni ions; and f, b and c are selected to meet the requirement of positive and negative charge balance.
10. A double metal cyanide catalyst prepared by the method for preparing a double metal cyanide catalyst by dynamic release according to any one of claims 1 to 9, characterized in that: The double metal cyanide catalyst is a compound of the general formula (III): 50 a [M b (CN) c ] d ·xL(H) e ·yT (III) Wherein, L is selected from the metal cation Zn 2+ , Fe 2+ , Cu 2+ 、Co 2+ 、Ni 2+ ,La 2+ Cr 2+ , Mn 2+ ; M is selected from one of Fe, Co, Mn, and Ni ions; H is Cl, Br, carbonate, sulfate, oxalate, cyanate, thiocyanate, C 1~4 One of carboxylate, nitrate and nitrite ions; T is an organic ligand selected from one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, octanol, octadecanol, ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol and mannitol; the selection of a, b, c, d and e meets the requirement of positive and negative charge balance; the value range of x is 0.5-2; the value range of y is 1-3.
Citation Information
Patent Citations
Catalyst complex
CN110869416B
Highly active double metal cyanide catalysts
US5482908A